Membangun Strategi Operasi melalui Budaya Organisasi Berbasis Tri Hita Karana untuk Mencapai Keunggulan Bersaing Berkelanjutan: Kasus pada Lembaga Perkreditan Desa di Kabupaten Buleleng - Adi Winata, IGK.; Windia, Wayan; Suartana, I Wayan (JURNAL MANAJEMEN AGRIBISNIS, 2015)
In general, the agricultural sector is still the main economic activity of the rural communities in Bali. Agribusiness systems in Bali are required to have high competitiveness in an era of economic modern. LPD as supporting institutions in the field of agribusiness in rural areas also face a high level of competition. o rganizational culture THK-based and operation strategy LPD in Buleleng is a unique resource for creating a sustainable competitive advantage. The purpose of this study was to determine the influence of organizational culture and operating strategies for sustainable competitive advantage LPD Buleleng regency. The number of LPD in Buleleng is 126 LPD spread across nine districts. Then the number of samples and the respondents are 45 people chairman of 45 LPD. Methods of data analysis using SEM-based General Structured Component Analysis (GSCA). O rganization c ulture-based Tri Hita Karana positive effect on the operating strategy of LPD in Buleleng. O rganization c ulture-based Tri Hita Karana and operating strategy positive effect on the sustainable competitive advantage LPD in Buleleng. This shows that organizational culture based Tri Hita Karana and operating strategy is a source of sustainable competitive advantage LPD in Buleleng. Management need to develop a linking strategy LPD operation between systems and procedures with a wig - awig . Awig - awig containing values of Tri Hita Karana, should be retained as the basis LPD operations. This may be the uniqueness of LPD in Buleleng, which is not owned by other financial institutions
Keywords: LPD, sustainable competitive advantage, organizational culture, tri hita karana and operation strategy